Investigation into the intracellular mechanisms whereby long-chain fatty acids protect the heart in ischaemia/reperfusion - Engelbrecht, Anna-Mart (Stellenbosch : Stellenbosch University, 2012)
Thessis (PhD)--Stellenbosch University, 2005.